2015
DOI: 10.1007/s12109-015-9404-9
|View full text |Cite
|
Sign up to set email alerts
|

Accessing, Reading and Interacting with Scientific Literature as a Factor of Academic Role

Abstract: This study was designed to examine the manner by which academic personnel including students, faculty, librarians and administrators, not only access and read scientific literature bust also interacts with it. In addition, the study examines whether there are differences in accessing, reading and interaction behavior between different groups in academia. Using an online survey, which was completed by 416 respondents worldwide, we found that PDF is the most common format for reading, downloading and saving. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
1
3
0
1
Order By: Relevance
“…The current result can also be associated with other studies that explored researchers' reading preferences (Halevi et al, 2015;Tenopir, 2003;Tenopir and King, 2002;Tenopir et al, 2009Tenopir et al, , 2012. These studies indicated a preference for printed materials.…”
supporting
confidence: 82%
“…The current result can also be associated with other studies that explored researchers' reading preferences (Halevi et al, 2015;Tenopir, 2003;Tenopir and King, 2002;Tenopir et al, 2009Tenopir et al, , 2012. These studies indicated a preference for printed materials.…”
supporting
confidence: 82%
“…Of course, social media and smartphones go hand in hand (Nicholas et al , ), so the increases in the former that we have already detected might result in similar increases in the latter. Resolution is getting better all the time, and screens are larger, and research published elsewhere indicates that academics now read more HTML web pages on their tablets, e‐readers, or smart phones compared to 2 years ago (Halevi, Moed, & Bar‐Ilan, ). In our sample, Chinese ECRs are the most active users of smartphones for scholarly purposes, using them particularly for discovery purposes (Nicholas et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…24 Rao, "Electronic Book Technologies: An Overview of the Present Situation." di komputer PC, dan hanya 2% yang membaca di tablet (Gambar 4).Penelitian terdahulu menunjukkan bahwa format PDF (Portable Document Format) adalah pilihan populer untuk membaca dan menyimpan artikel digital, dan orang pada umumnya membaca file PDF di komputer mereka (laptop atau desktop) 25 .Format PDF memiliki kompatibilitas yang tinggi, dan dapat dibaca dengan mudah oleh perangkat lunak lintas platform, sehingga dapat dibaca menggunakan berbagai gadget.…”
Section: Gadget Yang Digunakan Dalam Membaca Bahan Bacaan Akademikunclassified